Analysis Of Work Environment And Social Rewards On Employee Performance - Artiningsih, Dwi Wahyu; Shahrial Putra, Defin; Zamilah, Ervica (International Journal of Science, Technology & Management, 2022)
Changes in online learning conditions towards offline learning require readiness to create an atmosphere of togetherness and cohesiveness that is built for the common good. Changes at least provide knowledge and experience for the world of education that the environment is constantly changing. The Islamic University of Kalimantan (UNISKA) Muhammad Arsyad Al Banjari as the oldest and largest private university in South Kalimantan needs to pay attention to several factors including the work environment, non-physical environment and social rewards as an effort to improve employee performance.This research is explanatory research with a quantitative approach. The population of this research is UNISKA Banjarmasin education staff with a total sample of 52 people, the sampling technique is purposive sampling. Multiple linear regression analysis technique. The results showed that the physical work environment, nonphysical work environment and social rewards partially and simultaneously had a significant effect on employee performance in the UNISKA Banjarmasin environment. The research findings indicate that all physical conditions around the workplace are related to air temperature, lighting and layout. Relationships with leaders and relationships with fellow coworkers as well as relationships with subordinates are well-established/harmonious even though there is no increase in the form of financial impact on improving employee performance